Prestação de contas eleitoral : uma análise das prestações de contas dos candidatos a cargos eletivos nas eleições de 2020 vinculados a Comarca de Guaporé/RS - Decconto, Luis Henrique (2023)
The electoral accountability process has changed in recent years. One of the hallmarks of this is accounting, which starts to protect the information provided by candidates. Faced with this desire in the electoral process, electoral accounting is a way to increase the transparency and legitimacy of information provided to electoral justice. Therefore, the objective of this work was to analyze the accountability of the 2020 electoral period, specifically in the region of Guaporé/RS. The theme was addressed through documentary research, resorting to mathematical language to generate reflection, discussion and to describe the facts presented. The analysis of revenues and expenditures showed their adequacy to the current norms, as well as the approval of the rendering of accounts by the candidates for the position of councilor, which was 96.26% and the candidates for the position of mayors, which were 100%. Through the analysis carried out, it can be concluded that professionals in the accounting area are aware that the transparency of information is essential for the approval of accounts, but the low values of accounting fees practiced are highlighted, which can contribute to a lack of interest on the part of professionals. accounting in this branch of accounting.